2022
DOI: 10.3390/ani12243448
|View full text |Cite
|
Sign up to set email alerts
|

Improving Reproducibility to Enhance Scientific Rigor through Consideration of Mouse Diet

Abstract: Animal husbandry conditions, including rodent diet, constitute an example highlighting the importance of reporting experimental variables to enhance scientific rigor. In the present study, we examine the effects of three common rodent diets including two chows (Purina 5015 and Teklad 2019) and one purified ingredient diet (AIN-76A) on growth anthropometrics (body weight), behavior (nest building, actigraphy, passive avoidance) and blood biomarkers (ketones, glucose, amino acid profiles) in male and female C57B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Rest-activity rhythms were assessed as previously described [ 15 , 48 , 56 ]. Briefly, individually housed mice were tested under standard lighting conditions in home-made Plexiglas chambers containing passive infrared sensors mounted on the underside of the lids.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Rest-activity rhythms were assessed as previously described [ 15 , 48 , 56 ]. Briefly, individually housed mice were tested under standard lighting conditions in home-made Plexiglas chambers containing passive infrared sensors mounted on the underside of the lids.…”
Section: Methodsmentioning
confidence: 99%
“…Passive Avoidance: Learning and memory were assessed as previously described [ 11 , 48 , 56 ]. Specifically, mice were acclimated to the experimental room for at least 20 min prior to testing in a foot shock passive avoidance paradigm using an aversive stimulator/scrambler (Med Associates Inc., St. Albans, VT, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A hexokinase II knockdown study demonstrated significant effects of chow on mouse body weight, heart weight, and hexokinase phenotypes 9 . Another example comparing the effects of standard chow to a purified diet (AIN-76A) found that the chow diet drove differences in food intake and plasma essential amino acid levels in inbred C57BL/6 mice 10 . Lastly, differences in chow diets with variable fiber sources were found to induce differences in the distribution of gut bacterial communities in outbred CD-1 mice 11 .…”
Section: Introductionmentioning
confidence: 99%